Analisis Sistem Informasi Pariwisata Dalam Media Website Di Dinas Komunikasi Dan Informatika Kabupaten Teluk Wondama - jansen, joshua; Zulfikar, Ahmad (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2024)
The evolution of the current world of social media has increased people's interest in the destinations they visit. The tourism industry is a collection of tourism businesses that are interconnected to produce goods or services that meet the needs of tourists in tourism. This study aims to describe and analyze the development of tourism information systems in website media in Dinak Kominfo Teluk Wondama Regency, West Papua Province, and analyze inhibiting factors in the development of tourism information systems in website media in Dinak Kominfo Teluk Wondama Regency, West Papua Province. This study uses a descriptive qualitative method with an inductive approach. The informant is determined by the snowball sampling technique. Data collection is carried out by interviews, observation, and documentation. Data analysis techniques use data reduction, data presentation, and conclusions. The development of a tourism information system in the media website in Teluk Wondama Regency requires a comprehensive effort. Some efforts that need to be made include improving the quality of human resources, improving infrastructure, building partnerships with related parties, developing quality content, updating the technology used, and conducting periodic evaluations and improvements. The development of tourism information systems does not only involve technological aspects but also involves social and cultural aspects. Therefore, there needs to be synergy between technology and local wisdom so that the development of tourism information systems can run well and provide maximum benefits for local communities and visitors.